The Effect Of Corporate Social Responsibility On Firm Value With Good Corporate Governance As A Moderating Variable - Mutiara Amanda Putri Fathoni; Suwarno Suwarno (Universitas Riau Kepulauan, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) on company value and the role of Good Corporate Governance (GCG) as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2022–2024. The study uses a quantitative approach with secondary data analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results show that CSR does not have a significant effect on company value, and GCG is unable to moderate the relationship between CSR and company value. This study indicates that the implementation of CSR and the application of GCG are not yet fully perceived as factors that create economic value by investors.